Chinese Muslims (American Journal of Islam and Society, 2006)
Books Reviewed: Sachiko Murata, Chinese Gleams of Sufi Light: Wang Taiyu’s“Great Learning of the Pure and Real” and Liu Chih’s “Displaying theConcealment of the Real Realm.”Albany: SUNY Press, 2000; Maria Jaschokand Shui Jingjun, The History of Women’s Mosques in Chinese Islam: AMosque of Their Own. Richmond, UK: Curzon Press, 2000; Jean A. Berlie,Islam in China: Hui and Uyghurs between Modernization and Sinicization.Bangkok: White Lotus, 2004; Sheila Hollihan-Elliot, Muslims in China.Philadelphia: Mason Crest Publishers, 2006.With a population conservatively estimated at 20 million (and, according tosome sources, as high as 50 million), the Muslims of China remain one ofthe least studied and most misunderstood Muslim communities in theworld. After decades of relative neglect, however, over the past few yearsseveral books have been published that seek to shed light on differentaspects of the historic, religious, and contemporary lives of China’s Muslims.This review essay will survey four recent works written by a wide range ofscholars.Research on Islam in China has been hindered by many factors, includingthe difficulty of gaining expertise in both Chinese studies and Islamicstudies, learning both modern and classical Chinese and Arabic, the longstandingprejudices of Han Chinese scholars regarding the country’s minoritypeoples, together with the similarly long-standing prejudices of manywestern scholars regarding Islam. The earliest major work on the Muslimcommunities of China was published in 1910, by Marshall Broomhall of theChina Inland Mission. Titled Islam in China: A Neglected Problem, its mainpurpose was to educate Christian missionaries in China about the location,customs, and history of the indigenous Muslims in order to facilitate proselytizationactivities among them ...